PENGARUH KARAKTERISTIK SOSIAL EKONOMI WANITA PEDAGANG SAYUR TERHADAP KONTRIBUSI PENDAPATAN - Lili Winarti; Rokhman Permadi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Vegetable production is an agricultural business commodity that is quite in demand by farmers, with limited capital and resources, women farmers' wives must help their husbands to become vegetable traders and sell in the markets of the city of Kuala Pembuang. The purpose of this study was to analyze the influence of the socio-economic characteristics of women vegetable sellers on income contribution. This research was carried out in the City of Kuala Pembuang, from July to October 2022. The method used in this study was the census method with a total of 60 female vegetable sellers as respondents, with the sample criteria being female farmers' wives. Data analysis used is income analysis followed by a binary logit regression model, where Y which is a contribution has two dependent variables (dichotomy), and consists of 8 independent variables (age, number of dependents, education, length of household, farming experience, distance to market, income of vegetable sellers, and income of family members). The results showed that there were three socio-economic characteristic variables that had a significant effect on the income contribution, namely the number of dependents, the income of women traders and the income of family members.